Analysis of Religious Moderation Values in the Islamic Religious Education Textbook KMA 183 Of 2019 - Mashabi M. Noor Ritonga; Hasan Asari; Zaini Dahlan (South Sulawesi Education Development (SSED), 2024)
This research aims to determine the moderation values in the 2019 PAI KMA 183 textbook. This research uses qualitative research. This research uses a type of library research. The subject of this research is PAI KMA 183 textbooks including books on Fiqh, Aqidah Akhlak, Al-Quran and History of Islamic Culture. The findings of this research are as follows: (1). The 2019 KMA Islamic Religious Education Textbook contains the value of religious moderation. Overall, the material contained in PAI textbooks is in accordance with the needs of students in accordance with the 2013 curriculum (2). The content of religious moderation values in the Islamic Religious Education teaching book KAM 183 of 2019 is generally conveyed throughout the entire chapter. The values of religious moderation that often appear in these textbooks are: national commitment, non-violence, accommodating local culture and tolerance